ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION AT KAFE KUDU, JALAN SEI PETANI, MEDAN CITY - Najmus Tsaqib; Iskandarini; Beby Karina Fawzeea Sembiring (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of product quality and service quality on customer loyalty with customer satisfaction as a mediating variable at Kafe Kudu, Jalan Sei Petani, Medan City. The approach used is quantitative with the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The sample consisted of 90 respondents selected through purposive sampling. The results show that product quality does not have a significant effect on customer satisfaction but has a significant influence on customer loyalty. Conversely, service quality has a significant impact on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction significantly affects customer loyalty. Mediation testing indicates that customer satisfaction does not significantly mediate the relationship between product quality and loyalty but does significantly mediate the relationship between service quality and customer loyalty. These findings suggest that, in the context of Kafe Kudu, improving service quality is a more effective strategy for building customer satisfaction and loyalty than focusing solely on product quality. Therefore, management is advised to prioritize enhancing service quality as a long-term strategic effort.